Blanco DECam Bulge Survey (BDBS) III. A new view of the double red clump in the Milky Way bulge through luminosity and color distribution - Lim, Dongwook; Koch-Hansen, Andreas; Chung, C.; Johnson, C. I.; Kunder, A.; Simion, I. T.; Rich, R. M.; Clarkson, W. I.; Pilachowski, C. A.; Michael, S.; Vivas, A. K.; Young, M. D. (Astronomy and astrophysics, 2021)
Red clump (RC) stars are one of the best stellar tracers of the structure of the Milky Way (MW) bulge. Here we report a new view of the double RC through luminosity and color distributions of RC stars in nine bulge fields (l = 0.0°, ±4.5°; b = −6.0°, −7.5°, −9.0°) from the Blanco DECam Bulge Survey (BDBS), which covers near-ultraviolet to near-infrared bandpasses. The bright and faint RCs show contrasting distributions in (u − g)0 and (u − i)0 colors but similar distributions in (J − Ks)0 with a variation depending on the Galactic longitude, where the bright RC is typically redder than the faint RC. In particular, the RC stars are clearly divided into the bluer and redder populations when using the (u − g)0 color ((u − g)0 < 2.5 for the bluer RC; (u − g)0 ≥ 2.5 for the redder RC). The bluer stars show a single clump on the faint RC regime, whereas the redder stars form double clumps on both the bright and faint RCs. The bright clump of the redder stars is dominant in the positive longitude fields, while the faint clump of those red stars is significant at negative longitudes. We also confirm that the bluer and redder stars have different peak metallicity through comparison with spectroscopy (Δ[Fe/H] ∼ 0.45 dex). Therefore, our results support a scenario whereby the MW bulge is composed of a spheroid of metal-poor stars and a boxy/peanut shape (X-shape) predominantly made up of metal-rich stars.
Gesehen am 11.05.2021